State of the art of advanced solar control devices for buildings. (15th September 2017) - Kuhn, Tilmann E.
Highlights: The paper presents the state of the art of advanced solar control devices for buildings. It explains the state of the art of comparative evaluation of solar-control systems. It contains guidelines for the development of new solar control systems. Abstract: This paper deals with the state of the art of advanced solar control devices for buildings, with the comparative evaluation of solar-control systems and with guidelines for the development of new solar control systems. It includes multifunctional systems with building integrated photovoltaic (BIPV) and/or building integrated solar thermal (BIST) energy conversion. In order to facilitate and to structure the understanding of solar control systems two multidimensional spaces are introduced: the design space and the evaluation space. The design space contains the design parameters which are to be selected by the designer when solar control devices are to be chosen for specific buildings or when new systems are to be developed, such us the color of the slat of a venetian blind or the fraction of holes (direct transmittance) of a fabric for a roller blind. The evaluation space contains the performance parameters or evaluation criteria, which indicate the design's ability to satisfy the functional and aesthetic requirements, such us passive solar gain control or visual comfort. All the design parameters and evaluation criteria are explained in detail in the paper. A chapter with examples of advanced solar control systems completes the overview of the state of the art of solar control systems.